Body weight distortions in an auditory-driven body illusion in subclinical and clinical eating disorders - Ana Tajadura-Jiménez; Laura Crucianelli; Rebecca Zheng; Chloe Cheng; Judith Ley-Flores; Mercedes Borda-Más; Nadia Bianchi-Berthouze; Aikaterini Fotopoulou (Scientific Reports, 2022)
Abstract Previous studies suggest a stronger influence of visual signals on body image in individuals with eating disorders (EDs) than healthy controls; however, the influence of other exteroceptive sensory signals remains unclear. Here we used an illusion relying on auditory (exteroceptive) signals to manipulate body size/weight perceptions and investigated whether the mechanisms integrating sensory signals into body image are altered in subclinical and clinical EDs. Participants’ footstep sounds were altered to seem produced by lighter or heavier bodies. Across two experiments, we tested healthy women assigned to three groups based on self-reported Symptomatology of EDs (SED), and women with Anorexia Nervosa (AN), and used self-report, body-visualization, and behavioural (gait) measures. As with visual bodily illusions, we predicted stronger influence of auditory signals, leading to an enhanced body-weight illusion, in people with High-SED and AN. Unexpectedly, High-SED and AN participants displayed a gait typical of heavier bodies and a widest/heaviest visualized body in the ‘light’ footsteps condition. In contrast, Low-SED participants showed these patterns in the ‘heavy’ footsteps condition. Self-reports did not show group differences. The results of this pilot study suggest disturbances in the sensory integration mechanisms, rather than purely visually-driven body distortions, in subclinical/clinical EDs, opening opportunities for the development of novel diagnostic/therapeutic tools.